Системний аналіз освітніх моделей європейських країн з урахуванням входження в Болонський процес - Кудря, М. М. (НТУ "ХПІ", 2010)
В статье анализируются образовательные модели и опыт включения в Болонский процесс различных европейских стран: Франции, Венгрии, Ирландии, Швеции и Великобритании; рассматриваются квалификации разных уровней и структура ученых степеней.

In the article the author analyzes the educational models and the experience of joining the Bologne process of some European countries: France, Hungary, Ireland, Sweden and Great Britain, considers qualifications of different levels and the structure of educational grades.
The system analysis of educational models of the european countries in view of entry in Bolon process
Keywords: системи вищої освіти; принципи автономії; конкурентоспроможність; реформи; університети; наука